Representations of ideas of liberalism in jubilee (1863–1913) correspondence of newspaper «Russkie Vedomosti» - M. K. Churkin (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the problem of presenting liberal projects, moods, ideas in the anniversary discourse, in speeches, appeals, letters, telegrams about the fiftieth anniversary of the newspaper «Russkie Vedomosti». The purpose of the work is to reconstruct the communication channels of the publication and the audience. The study found that jubilee celebrations contributed to the intensification of interaction between the addressee and recipients, identifying a circle of active supporters of moderate liberalism and increasing the influence of liberal ideas on Russian society